CONCEPTUALIZATION OF SOCIAL CAPITAL IN CROSS-SECTIONAL DESIGN STUDIES: RAPID REVIEW OF LITERATURE - Šuriņa, Sanita; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Social capital is a concept that is widely studied in different fields of science, in different dimensions of this concept, and consists of a number of elements, including trust, sense of belonging and affiliation. Given the multidimensional nature of social capital, researchers point to the challenges of its conceptualization and operationalization of its elements. Objective: To identify cross-sectional design studies, with nationally representative samples from European countries, where each study assessed following social capital elements: either trust and sense of belonging, or trust and affiliation, to identify other included social capital elements, to clarify how these elements are operationalized, to identify what social capital determinants are taken into account and what social capital manifestations have been evaluated.Method: Cross-sectional design studies, with nationally representative samples for European countries, conducted between 2014 and 2019, were sought in Science Direct, ProQuest, SAGE, EBSCO, Google Scholar, using the key words “social capital”, “trust”, “sense of belonging” and their synonyms. The methodological quality was assessed by Appraisal tool for Cross-Sectional Studies (Axis). Results: From initially identified 173 studies, the literature review included 3 studies. The included studies identify determinants of social capital (socio-demographic factors (2 studies) and political affiliation (1 study)) and manifestations of social capital (self-rated health (1 study), loneliness (1 study), willingness to pay for environmental quality (1 study)). The included studies define the bonding, bridging and linking types of social capital, as well as the structural and cognitive dimensions of social capital. The studies assessed and operationalized the following social capital elements: trust (3 studies), sense of belonging (1 study), support (1 study), frequency of contacts (2 studies), participation in associations (1 study), religious affiliation (1 study), civic activity (2 studies).